Effects of ground motion modification methods and ground motion duration on seismic performance of a 15-storied building. (January 2018) - Samanta, Avik; Pandey, Pranjul
Abstract: Present day seismic analysis of structures use non-linear time-history analysis to reproduce the actual behavior of a structure under the action of ground motions. Adequate ground motion records are important to perform time-history analysis properly and real recorded ground motions are generally modified or scaled for such analysis. The need to modify and scale the ground motion time histories to the target hazard of a site of interest calls for an assessment of available scaling and matching techniques. Moreover seismic codes and guidelines in India or other countries do not consider the effect of duration on the seismic response of structure. A fifteen storied building is considered in this study. The modeling and nonlinear time history analysis is performed using SAP2000. Four ground motion modification methods are used: Geometric mean, Sa(T1) scaling, RSPMATCH and Seismosoft matching method. Structural responses are studied both for short and long duration earthquake ground motions. Highlights: Effects of ground motion modification methods on seismic performance of a building. Effects of ground motion duration on seismic performance of a building. Ground motion modification method affects structural response variable. Peak story drift ratio is not affected by ground motion duration.